Shifts in California Statewide Cellulitis Hospitalization Rates were Found Between 2017 to 2022 Using a Retrospective Analysis - Scheinkman, Ryan; Ravipati, Advaitaa; Pulumati, Anika; Green, Daniel; Jean-Pierre, Philippe; Nouri, Keyvan (International Journal of Medical Students, 2025)
BACKGROUND: Cellulitis accounts for 3.7 billion in ambulatory healthcare costs. We wanted to determine statewide trends for inpatient cellulitis cases as well as anatomic distribution of cases. METHODS A retrospective analysis was performed using California’s Department of Health Care Access and Information’s “Hospital Inpatient - Diagnosis, Procedure, and External Cause Codes. Codes were extracted relevant to cellulitis, analyzed in excel to compile data on temporal trends and summating anatomical distribution over the timespan of 2017-2022. RESULTS: We found 986,655 cases of inpatient cellulitis over the time frame with a nadir during 2020 (151,100 cases) and a peak at 2019 (175,360 cases). The anatomic location with the highest prevalence of cellulitis was the lower limbs (295,913 in right lower limbs, 295,162 cases in left lower limbs over the timeframe). CONCLUSION: The shifts in patient cases may be due to changes in access to care during the COVID-19 pandemic that could inform future care during future pandemics. Additionally, the anatomical locational distribution favoring the lower limbs could be explained by preponderance of wound generation in this region. Future research could evaluate factors such as wound severity in a similar patient cohort in relation to anatomic location as well as analyzing epidemiological factors that could better explain the temporal trends observed around 2020